Promoting teaching and learning performance in mathematics classroom through e-learning - Tribhuwan Kumar, Salman Sahud Alotaibi, (Opción, 1970)
This delectable research project studies the practice of e-learning in Mathematics classroom. It propagates the wide concept of e-learning, its dimensions, advantages and applications in Mathematics. The innovation of the Information Communication Technology (ICT) in modern teaching is powerful approach which has brought magical response across the globe. E-learning has various implications like digital Technology. In traditional Mathematics class it may be used as buttress of the traditional face to face lecture. However, e-learning shall be integrated cautiously without completely abandoning old methods.